Analysis of the influencing factors on the tribological properties of peanut straw - Wang, Xiaoyu; Li, Guoming; He, Xin; Yang, Rusha; Peng, Qiangji; Zhang, Chunyan; Zhang, Ningning; Kang, Jianming (International Journal of Agricultural and Biological Engineering, 2024)
Chopped straws can help replenish soil nutrients, improve soil structure, and increase the amount of organic matter contained in soil. The grinding ability of crop straws is influenced by the frictional characteristics of the materials involved in the grinding process. Studying the frictional properties of peanut stem, residual film, and external contact material is essential tounder standing the grinding action of peanuts. This study discussed the frictional properties between films and between residual film and external contact materials. A physical test was conducted using a friction coefficient detector. The results showed thatthe average value of the dynamic sliding friction coefficient (fk) was 0.34, the average value of the static sliding friction coefficient (fs) between the film and the 40Cr steel plate (as the external contact material) was 0.38, and the average fs value between the films and between the residual film and the external contact material was 0.36. Based on the Box-Behnken test, second-order response models were established for the static rolling stability angle (μe) and the static sliding friction coefficient (fs). On the basis of establishing the static rolling stability angle (μe) and static sliding friction coefficient (fs) of the evaluation index, the different friction characteristics between straw and external contact materials were investigated under varying moisture content, external contact materials and particle sizes. The study results can provide a basis for the development of equipment that can be used for peanut straw crushing and membrane separation.Keywords: peanut straw, residual film, friction characteristicsDOI: 10.25165/j.ijabe.20241706.9114Citation: Wang X Y, Li G M, He X, Yang R S, Peng Q J, Zhang C Y, et al. Analysis of the influencing factors on the tribological properties of peanut straw. Int J Agric & Biol Eng, 2024; 17(6): 76–85.